Comparison of electrocardiogram characteristics and pacing parameters between left bundle branch pacing and right ventricular pacing in patients receiving pacemaker therapy. Issue 4 (20th November 2018) - Chen, Keping; Li, Yuqiu; Dai, Yan; Sun, Qi; Luo, Bin; Li, Chao; Zhang, Shu
Abstract: Aims: This study explores the feasibility of left bundle branch pacing (LBBP) and characterizes electrocardiogram (ECG) patterns during the pacing in comparison with conventional right ventricular pacing (RVP). Methods and results: Forty pacing-indicated patients were prospectively enrolled. Twenty patients underwent LBBP (the LBBP group), and 20 patients underwent RVP (the RVP group). Left bundle branch pacing was achieved by transseptal method in the basal ventricular septum. Electrocardiogram characteristics, pacing parameters, pacing sites, and safety events were assessed at implantation and 3-month follow-up. In the LBBP group, the pacing lead was successfully placed near the endocardium of the left side of the septum. Electrocardiogram pattern during LBBP showed right bundle branch conduction delay. Left bundle branch block (LBBB) in two patients was corrected by LBBP. Post-implantation 3D echocardiography confirmed the pacing location. In the RVP group, ECG showed LBBB pattern. The paced QRS duration was 111.85 ± 10.77 ms in LBBP group and 160.15 ± 15.04 ms in the RVP group ( P < 0.001). Pacing thresholds (at implantation: 0.73 ± 0.20 V in the LBBP group and 0.61 ± 0.23 V in the RVP group) remained low and stable at 3-month follow-up. No adverse event was observed during 3-month follow-up. Conclusion: This study demonstrates the clinical feasibility of LBBP. Left bundle branch pacing that has a low pacing threshold and produces narrow ECG QRS duration may be a new pacing strategy for patients in need of ventricular pacing.